(untitled) - Pervin Kurtoglu; Sevinc Tastan; Servet Tunay (University of Ostrava, 2020)
Aim: The aim of this quantitative study was to assess falls and fear of falling in patients with knee osteoarthritis, and to determine their effects on daily activities. Design: A descriptive and prospective quantitative study. Methods: The study employed a descriptive and prospective design, examining 93 patients with knee osteoarthritis. We used the Lequesne Index (LI), the Falls Efficacy Scale (FES), and the Visual Analog Scale for Fear of Falling (VAS-FOF) to assess the effects of falls and fear of falling on daily activities. Results: The mean age of participants was 62.0 years old. In total, 78.5% of patients had experienced falls in the past, 53.4% of whom were admitted to hospital as a result. There was a positive significant correlation between total mean Lequesne Index and VAS-FOF scores, age, and BMI of participants (r = 0.310; r = 0.231; r = 0.283) (p < 0.05). A negative correlation was found between FES and VAS-FOF scores, total LI score, and age (p < 0.05). In addition, a negative significant correlation was found between age and BMI (r = -0.257) (p < 0.013). Conclusion: The results demonstrated that fear of falling affects the performance of daily activities. Knee osteoarthritis is an important risk factor for falling, and falls affect daily activities in those with knee osteoarthritis.